A ação governamental e as empresas de pequeno porte: práticas gerenciais no município do Rio de Janeiro - Costa, Marília Magarão (1997)
The value of the small-size business contribution for development of the country is enough to make this entrepreneurial segment to be consider in the strategy of public policies. In Brazil, the hindrance that prevent small-size business from benefiting from these policies results mainly from the definition of what means small-size, the tax system and the social charges. To overcome such limitations and survive, small entrepreneurs adopt management practices for avoiding taxes payment with unfavourable consequences for the enterprise and society. Such practices as the use of caixa dois and the payment of unregistered wages are widely used by small business. They prefer to run the risk of inspection rather than fulfill the legal requirements. In order to reverse this situation, the government strategy for small business should favour the creation and growth of an entrepreneurial class, the improvement of managerial capacity, the simplification of laws with an reduction of social charges, and the absorption of excess of man-power by the market.